Effects of different operating parameters in papaya halwa drying - Lau, Fui Fui; Taip, Farah Saleena (Universiti Putra Malaysia Press, 2011)
An experimental study was performed to determine the drying characteristics of dried papaya using different drying methods. They were dried using several methods, such as sun drying, solar drying, oven drying, and microwave drying. The effects of different operating conditions on physical quality attributes were investigated. The papaya were cut into different thicknesses and cooked in sugar syrup with different sugar concentration for 24 hours. Three different temperature settings were used in oven and microwave drying. The drying curve and drying rate of each method, temperature, sample thickness and sugar concentration were studied. The drying times were found as in 6-15 minutes, 5 to 11 h, 10 to 18 h, and 14 to 23 h for the microwave, oven, sun and solar drying, respectively. The drying time increased with the increase of sample thickness and sugar concentration, as well as with the decrease of the drying temperature. In this study, quality attributes like colours and textural property of dried papaya were explored. Among the various methods of the drying characteristics of papaya halwa, oven drying was preferred with the optimum sample in 5 mm thickness and at the air temperature of 70oC as it saved up to 40% of the drying time as compared to other methods, except microwave, and produced acceptable physical quality of product.